Gender differences in Parkinson's disease depression. (March 2017) - Perrin, Andrew J.; Nosova, Ekaterina; Co, Kim; Book, Adam; Iu, Oscar; Silva, Vanessa; Thompson, Christina; McKeown, Martin J.; Stoessl, A. Jon; Farrer, Matthew J.; Appel-Cresswell, Silke
Abstract: Introduction: 30–40% of patients with Parkinson's disease (PD) experience depression during their illness; identifying subtypes of depression and groups at risk remains a challenge in routine clinical care. One avenue that remains underexplored is the gender-specific profiles manifested in PD depression. We sought to explore this in a large sample of clinical PD patients. Methods: 307 patient records at a tertiary referral centre were reviewed for clinical and demographic factors. We used recursive partitioning to determine which items on the Beck Depression Inventory (BDI) were most useful in differentiating patients who scored in the depressed range (≥14) from those who scored in the non-depressed range (≤13). We also used recursive partitioning to identify those BDI items that were most effective in differentiating depressed from non-depressed patients in both genders. Results: We were able to identify a subset of items on the BDI that were most useful in partitioning depressed from non-depressed in the entire cohort. Partitioning of men and women with PD depression relied on different key BDI items, melancholy featuring prominently in women, while the more classical factors associated with depression in PD (apathy and loss of libido) featured more prominently in men. Conclusion: Unique factors not previously identified as core features of depression in PD were found most useful in partitioning depressed women from non-depressed women. This raises the possibility that a female-specific depressive profile has been under-appreciated in past work. Additional studies are required to discern how this may impact future research, diagnosis and treatment. Highlights: Partitioning of men and women with PD depression relied on different key BDI items. Women were partitioned most effectively using mood and negative self-image. Men were partitioned most effectively using loss of sexual drive and apathy.